Surgery Guidelines In Covid-19 Pandemic; Bangladesh Perspective - Bhuiyan, Md Nur Hossain; Akhter, SM Quamrul; Hossain, AZM Mostaque; Alam, AHM Towhidul; Khan, Zulfiqure Rahman; Barua, Kanak Kanti (Journal of Surgical Sciences, 2021)
Abstract not available Journal of Surgical Sciences (2020) Vol. 24 (2) : 70-76